2018
DOI: 10.1093/schbul/sby165
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Frontostriatal Connectivity in Negative Symptoms of Schizophrenia

Abstract: Negative symptoms represent a distinct component of psychopathology in schizophrenia (SCZ) and are a stable construct over time. Although impaired frontostriatal connectivity has been frequently described in SCZ, its link with negative symptoms has not been carefully studied. We tested the hypothesis that frontostriatal connectivity at rest may be associated with the severity of negative symptoms in SCZ. Resting state functional connectivity (rsFC) data from 95 mostly medicated patients with SCZ and 139 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Combining previous reports and our results suggests that increased connectivity in the FES with the risk allele group may be a compensatory mechanism for the relatively inefficient connectivity of the relevant brain regions to reach near-normal performance (17). Consistent with a recent task-independent fMRI study, we also found abnormal orbitofrontal-putamen functional connectivity in schizophrenia but failed to associate connectivity with the severity of negative symptoms in that study (18). Few previous reports have mentioned abnormal orbitofrontal-pallidum connectivity in schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Combining previous reports and our results suggests that increased connectivity in the FES with the risk allele group may be a compensatory mechanism for the relatively inefficient connectivity of the relevant brain regions to reach near-normal performance (17). Consistent with a recent task-independent fMRI study, we also found abnormal orbitofrontal-putamen functional connectivity in schizophrenia but failed to associate connectivity with the severity of negative symptoms in that study (18). Few previous reports have mentioned abnormal orbitofrontal-pallidum connectivity in schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Specific prefrontal areas, in particular, the dorsolateral prefrontal cortex (DLPFC), have been identified 10 . More recent studies have suggested that patients with NSS have structural and functional impairments in prefrontal areas and that the connectivity between those areas and the rest of the brain, including striatal regions, is also impacted 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral and neuroimaging studies tend to show the underpinnings of these clinical differences (7, 11). Reduced frontostriatal functional connectivity associated with negative symptoms might provide a supplementary hypothesis to study the neurobiological mechanisms of negative symptoms (16).…”
Section: Introductionmentioning
confidence: 99%